PERAN KUALITAS PRODUK DALAM MEMEDIASI HUBUNGAN HARGA TERHADAP NIAT BELI LAPTOP ASUS DI KOTA DENPASAR - Damayana, JJC Rangga; Rahyuda, Ketut (E-Jurnal Manajemen; Vol 7 No 9 (2018), 2018)
The purpose of this study is to explain the effect of price on the purchase intention of ASUS brand Laptop product with product quality variable as the mediating variable in Denpasar City. The variables studied in this study are variable price, product quality and purchase intention. The number of samples taken as many as 120 teens to adults who have never bought ASUS products, using non-probability random sampling method in the form of purposive sampling. Data were collected through questionnaires. The analysis technique used is the test of sobel by using path analysis. Based on the results of the analysis found have a positive and significant on that price variables effect on the purchase intention ASUS brand laptop products in Denpasar City, price variabels have a positive and significant effect on product quality on ASUS brand Laptop products, product quality variables have a positive and significant effect on purchase intention of Laptop product ASUS brand in the city of Denpasar, product quality variables mediate effect of the price on purchase intention of ASUS brand Laptop in Denpasar City. Keyword : purchase intention, price, product quality